Metals in E Waste Causing Concerns in Bihar (International Journal of Engineering and Computer Science, 2015)
Growth of electric & electronic equipments (EEE) with given rate of obsolesce the pool of obsolete EEE is day by getting to adimension where its disposal is becoming challenge. The constituents in terms of elemental and manmade materials make ithazardous and toxic which required technological disposal. The availability of 5 % formal sector leaving remaining 95 % ininformal sector for crude and unscientific disposal is depleting the environment and degrading the atmosphere where we livein.The health concerns of persons directly involved in handling these disposals in particular and population in general is atthreat from these unlawful activities. National demography, economic strata and consumerisation trends are different fordifferent states and cities and localities. In view of these factors when case study for getting the level of contamination due toelements available in these EEE disposed products burial places and knowhow of measures reveals that in case of Bihar citiesthe contamination levels are inching towards the worst affected parts of globe situation. Knowhow and regulating mechanismand information towards these are at minimal level and mass education and concerns is need of hour.